The transcription factor Foxp1 preserves integrity of an active Foxp3 locus in extrathymic Treg cells - Sayantani Ghosh (Nature Portfolio, 2018)
Regulatory T (Treg) cells suppress immune cell activation to maintain immune homeostasis, and have their lineage enforced by the master transcription factor Foxp3. Here the authors show that Foxp3 expression is promoted and maintained by a related family member, Foxp1, specifically in peripherally induced Treg but not in Treg cells of thymic origin.